The effect of transformational leadership on voice behavior in the hospitality industry - Suryandari Istiqomah; Sarwoto Sarwoto; Wahyu Trinarningsih (Jurnal Manajemen dan Pemasaran Jasa, 2022)
The COVID-19 pandemic had an impact on all service industries, specifically hospitality, which has become increasingly competitive. Therefore, innovation and service improvement are needed to provide the best service for consumers by determining the voice behavior of their employees. This study examines the effect of transformational leadership on employee voice behavior, specifically frontline at hotels in Central Java. The mediating variables consisting of work and engagement were used to clarify the mechanism related to the effect of transformational leadership on voice behavior. The sampling technique used in this research is purposive sampling, namely by using the criteria of frontline employees who have worked for at least 1 year. Data were collected from 216 frontline employers at hotels and analyzed using the SEM PLS. The result showed that transformational leadership and work engagement can indirectly promote employee voice behavior. Furthermore, the meaning of work can promote voice behavior with a longer mechanism through work engagement.